Genetic modifiers of folate, vitamin B-12, and homocysteine status in a cross-sectional study of the Canadian population. Issue 6 (6th May 2015) - Zinck, John WR; de Groh, Margaret; MacFarlane, Amanda J
ABSTRACT: Background: Genetic variation can cause variable responses to environmental stimuli. A number of single-nucleotide polymorphisms (SNPs) have been associated with B vitamin status or chronic diseases related to vitamin B-12 and folate metabolism. Objective: Our objective was to identify associations between common SNPs in genes related to folate and vitamin B-12 metabolism or associated with B vitamin–related chronic diseases and biomarkers of nutrient status in a population exposed to folic acid fortification. Design: A panel of 116 SNPs was sequenced by using the Sequenom iPLEX Gold platform in a sample of 3114 adults aged 20–79 y from the Canadian Health Measures Survey, cycle 1. Associations between these SNPs and red blood cell (RBC) folate, serum vitamin B-12, and plasma total homocysteine were determined. Results: Twenty-one SNPs and 6 haplotype blocks were associated with RBC folate, serum vitamin B-12, and/or plasma homocysteine concentrations. Vitamin status was associated mainly with SNPs in genes directly involved in vitamin absorption/uptake ( CUBN, CD320 ), transport ( TCN1, TCN2 ), or metabolism ( BHMT2, CBS, MTHFR, MUT, SHMT1 ). Other SNPs included those in the DNMT2, DPEP1, FUT2, NOX4, and PON1 genes. Conclusions: We identified novel associations between SNPs in CD320 and DNMT2, which had been previously associated with neural tube defects, and vitamin B-12 status, as well as between SNPs in SHMT1, which had been previously associated with colorectal cancer and cardiovascular disease risk, and RBC folate status. These novel associations provide a plausible metabolic rationale for the association of these SNPs with B vitamin–related diseases. We also observed a novel association between an SNP in CUBN with RBC folate and confirmed the association of a number of SNPs with B vitamin status in this large cross-sectional study.